2019
DOI: 10.3390/s19235107
|View full text |Cite
|
Sign up to set email alerts
|

Low Voltage High-Energy α-Particle Detectors by GaN-on-GaN Schottky Diodes with Record-High Charge Collection Efficiency

Abstract: A low voltage (−20 V) operating high-energy (5.48 MeV) α-particle detector with a high charge collection efficiency (CCE) of approximately 65% was observed from the compensated (7.7 × 1014 /cm3) metalorganic vapor phase epitaxy (MOVPE) grown 15 µm thick drift layer gallium nitride (GaN) Schottky diodes on free-standing n+-GaN substrate. The observed CCE was 30% higher than the bulk GaN (400 µm)-based Schottky barrier diodes (SBD) at −20 V. This is the first report of α–particle detection at 5.48 MeV with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A summary of important material characteristics has been listed in Table 1 below. Ga-45 N-109 [10] 35 [11] Bias Voltage Required to achieve 100% CCE (V) 24 [12] 150 [13] 200 [14] 300 [15] 15 [16] Detected Si-based radiation detectors-Si has a decently high E d of 13 eV accompanied by a well-developed device fabrication technology [8]. While high E d results in a good life-time of the detector, the established fabrication technology is important to fabricate detectors with wide DW and low leakage currents.…”
Section: Properties Of Selected Semiconductorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of important material characteristics has been listed in Table 1 below. Ga-45 N-109 [10] 35 [11] Bias Voltage Required to achieve 100% CCE (V) 24 [12] 150 [13] 200 [14] 300 [15] 15 [16] Detected Si-based radiation detectors-Si has a decently high E d of 13 eV accompanied by a well-developed device fabrication technology [8]. While high E d results in a good life-time of the detector, the established fabrication technology is important to fabricate detectors with wide DW and low leakage currents.…”
Section: Properties Of Selected Semiconductorsmentioning
confidence: 99%
“…From Table 3, it can be observed that higher energy has been detected by sandwich structures but they require high reverse voltage bias conditions for successful operation. To overcome the high-voltage requirement of a sandwich structure, a low CCD epitaxial layer on highly doped GaN substrate could be used [15]. The low CCD epitaxial layer helps to operate the detector at lower voltages however, highly doped substrate helps to form a low resistance Ohmic contacts.…”
Section: Schottky Barrier Diodesmentioning
confidence: 99%
See 1 more Smart Citation
“…24) At low reverse bias voltages (<−20 V), we have observed change in CM from TFE to thermionic emission (TE) with the increase in DL thickness. 25) Although SBDs with 15 μm DL exhibited 65% of charge collection efficiency (CCE) for alpha-particle detection at −20 V. It also required higher voltages (> −300 V) to increase the DW of SBDs and achieve 96% of CCE. 25) The study of high voltage (HV) CM at elevated temperatures are worthy and important to understand the overall performance of the fabricated SBDs.…”
mentioning
confidence: 99%
“…25) Although SBDs with 15 μm DL exhibited 65% of charge collection efficiency (CCE) for alpha-particle detection at −20 V. It also required higher voltages (> −300 V) to increase the DW of SBDs and achieve 96% of CCE. 25) The study of high voltage (HV) CM at elevated temperatures are worthy and important to understand the overall performance of the fabricated SBDs. Moreover, the HV conditions are necessary for the generation of thick DW, which improves sensitivity of the detector.…”
mentioning
confidence: 99%